Cognitive Reappraisal as a Mediating Mechanism Between Mindfulness and Stress Reduction - Critchley , Sue J; Bordelon , Curry; Schwarzenberger , Molly (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The objective of this study was to examine whether cognitive reappraisal mediates the relationship between mindfulness and stress reduction among Canadian adults. Methods and Materials: A descriptive correlational design was applied with a sample of 399 participants selected according to the Morgan and Krejcie table. Standardized instruments were used to measure mindfulness (Five Facet Mindfulness Questionnaire), cognitive reappraisal (Cognitive Emotion Regulation Questionnaire – Reappraisal subscale), and stress (Perceived Stress Scale). Data were analyzed using SPSS version 27 for descriptive statistics and Pearson correlations, followed by Structural Equation Modeling (SEM) in AMOS version 21 to test the hypothesized mediating model. Model fit was evaluated using χ², GFI, AGFI, CFI, TLI, and RMSEA indices. Findings: Pearson correlation results indicated that mindfulness was significantly and positively associated with cognitive reappraisal (r = .47, p < .001) and negatively related to perceived stress (r = –.54, p < .001). Cognitive reappraisal was also significantly and negatively associated with stress (r = –.39, p < .001). The structural model demonstrated excellent fit (χ²/df = 1.92, GFI = .94, AGFI = .91, CFI = .97, TLI = .96, RMSEA = .048). SEM results confirmed significant direct paths from mindfulness to reappraisal (β = .45, p < .001), reappraisal to stress (β = –.23, p = .002), and mindfulness to stress (β = –.36, p < .001). The indirect effect of mindfulness on stress through reappraisal was also significant (β = –.10, p = .004). Overall, the total effect of mindfulness on stress reduction was strong (β = –.46, p < .001). Conclusion: The findings demonstrate that cognitive reappraisal partially mediates the effect of mindfulness on stress reduction, confirming that mindfulness not only directly lowers stress but also exerts indirect effects by enhancing adaptive emotion regulation strategies.